Construction of a highly saturated genetic map and identification of quantitative trait loci for leaf traits in jujube - Yan, Fenfen; Luo, Yujia; Bao, Jingkai; Pan, Yiling; Wang, Jiurui; Wu, Cuiyun; Liu, Mengjun (Frontiers in Plant Science, 2022)
Chinese jujube (Ziziphus jujuba Mill.), a member of the genus Ziziphus, which comes under the family Rhamnaceae, is the most important species in terms of its economic, ecological, and social benefits. To dissect the loci associated with important phenotypical traits and analyze their genetic and genomic information in jujube, a whole-genome resequencing (WGR) based highly saturated genetic map was constructed using an F1 hybrid population of 140 progeny individuals derived from the cross of ‘JMS2’ × ‘Jiaocheng 5’. The average sequencing depth of the parents was 14.09× and that of the progeny was 2.62×, and the average comparison efficiency between the sample and the reference genome was 97.09%. Three sets of genetic maps were constructed for a female parent, a male parent, and integrated. A total of 8,684 markers, including 8,158 SNP and 526 InDel markers, were evenly distributed across all 12 linkage groups (LGs) in the integrated map, spanning 1,713.22 cM with an average marker interval of 0.2 cM. In terms of marker number and density, this is the most saturated genetic map of jujube to date, nearly doubling that of the best ones previously reported. Based on this genetic map and phenotype data from 2019 to 2021, 31 leaf trait QTLs were identified in the linkage groups (LG1, 15; LG3, 1; LG5, 8; LG7, 4; LG8, 1, and LG11, 2), including 17 major QTLs. There were 4, 8, 14, and 5 QTLs that contributed to leaf length, leaf width, leaf shape index, and leaf area, respectively. Six QTLs clusters were detected on LG1 (8.05 cM–9.52 cM; 13.12 cM–13.99 cM; 123.84 cM–126.09 cM), LG5 (50.58 cM–50.86 cM; 80.10 cM–81.76 cM) and LG11 (35.98 cM–48.62 cM). Eight candidate genes were identified within the QTLs cluster regions. Annotation information showed that 4 genes (LOC107418196, LOC107418241, LOC107417968, and LOC112492570) in these QTLs are related to cell division and cell wall integrity. This research will provide a valuable tool for further QTL analysis, candidate gene identification, map-based gene cloning, comparative mapping, and marker-assisted selection (MAS) in jujube.